2018
DOI: 10.1111/1440-1681.13042
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐101a ameliorates AngII‐mediated hypertensive nephropathy by blockade of TGFβ/Smad3 and NF‐κB signalling in a mouse model of hypertension

Abstract: Primary hypertension (essential hypertension or idiopathic hypertension) is regarded as the most common type of hypertension and affects 95% of hypertensive patients. 1 Primary hypertension is a crucial risk factor of cerebral, cardiac, and renal events. Moreover, hypertensive nephropathy is one of the most lethal complications of primary hypertension. Recently, more and more evidence has shown that high blood pressure may cause tubular cell damage and tubulointerstitial fibrosis. In addition, high blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…fibrosis (37), suggesting that inhibiting TGFβri may be a promising anti-fibrotic therapeutic strategy for DN. These findings are consistent with the current study where it was found that circrna_0000491 knockdown inhibited TGFβ1, TGFβri and pSmad3 protein expression levels (34,36).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…fibrosis (37), suggesting that inhibiting TGFβri may be a promising anti-fibrotic therapeutic strategy for DN. These findings are consistent with the current study where it was found that circrna_0000491 knockdown inhibited TGFβ1, TGFβri and pSmad3 protein expression levels (34,36).…”
Section: Discussionsupporting
confidence: 93%
“…In this pathway, TGF-β1 exerts biological effects through binding to type II β-β receptor and subsequently recruits and activates TGFβRI, then the activated TGFβR1 phosphorylates Smad2/3 ( 33 , 34 ). Previous studies have demonstrated that inhibiting TGFβRI significantly improves various disease, including pulmonary fibrosis ( 35 ), hypertensive nephropathy ( 36 ) and tubulo-interstitial fibrosis ( 37 ), suggesting that inhibiting TGFβRI may be a promising anti-fibrotic therapeutic strategy for DN. These findings are consistent with the current study where it was found that circRNA_0000491 knockdown inhibited TGFβ1, TGFβRI and pSmad3 protein expression levels ( 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the anti-fibrotic properties of galunisertib have not been widely explored, there is an emerging evidence for its therapeutic efficacy in liver fibrosis [26,27]. To date, the only report showing a potential benefit of galunisertib for the treatment of renal fibrosis in vivo is the study by Ding et al [90]. This study demonstrated that co-administration of angiotensin II and galunisertib significantly improved renal function in a murine model of hypertensive nephropathy; however, no fibrosis parameters were evaluated.…”
Section: Galunisertibmentioning
confidence: 99%
“…In addition, it has reported that AMPK activation promotes the entry of nuclear factor erythroid 2-related factor-2 (Nrf2) into the nucleus, up-regulates the expressions of antioxidant factors such as heme oxygenase-1 (HO-1) and NAD (P) H:quinone oxidoreductase (NQO-1), thus exerting the effect of antioxidant stress (Ni, Shen et al, 2019;Yamakage, Tanaka et al, 2020). Notably, the injury of renal tubular epithelial cells induced by releasing of in ammatory mediators and oxidative stress plays a key role in the pathogenesis of hypertensive nephropathy (Ding, Zhou et al, 2019;Zhang, Cheng et al, 2020). Moreover, a study shown that FGF21 prevented type 2 diabetic-induced cardiomyopathy through activation of AMPK-mediated antioxidation and lipid-lowering effects (Yang, Feng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%